A Fatal Case of Congenital Langerhans Cell Histiocytosis with Disseminated Cutaneous Lesions in a Premature Neonate - Michio Inoue; Yoko Tomita; Tsuyoshi Egawa; Tomoaki Ioroi; Masaaki Kugo; Shinsaku Imashuku (Case Reports in Pediatrics)
Background. The outcome of neonates with congenital cutaneous Langerhans cell histiocytosis (LCH) is variable. Observations. We report a case of LCH in a female premature neonate born at 33-week gestation. She had disseminated cutaneous lesions, which consisted of hemorrhagic papules and vesicles, with sparse healthy skin areas, and the hands and feet were contracted with scarring and blackened. She was in respiratory failure although no apparent pulmonary or bone lesions on X-rays were noted. Skin biopsy confirmed a diagnosis of LCH due to observation of CD1a+ Langerhans cells, which lacked expression of E-cadherin and CD56. The patient died 57 hours after birth. Conclusions. Based on this case and the literature survey, the outcome of premature babies with congenital cutaneous LCH lesions is noted to be unfavorable, with the majority of such cases suffering from multisystem disease.